Identification of Soil Salinity Due to Seawater Intrusion on Rice Field in the Northern Coast of Indramayu, West Java - Erfandi, Deddy; Rachman, Achmad (JOURNAL OF TROPICAL SOILS, 2011)
The rice fields in Indramayu district is 55% of the district area. The average rainfall is 1590 mm per year. Most lands on the North Coast of Java (northern) were potentially affected by sea water intrusion. Extensive observations were 102.321 ha. Field observations were done by survey method. Observations had been conducted on rice fields Pantura, Indramayu, West Java. Soil salinity was measured by using the electromagnetic conductivity meter (EM-38). The results revealed that area had very high salinity which was 22.57%, closest to the beach Indramayu. In the South Region, soil salinity was lower, in accordance with the distance from the coastline. Some areas had a low, medium, and high salinity status in which 58.41%, 8.54% and 10.49%, respectively. Much of the research area had very high Sodium (Na) and ECe (0 - 30 cm) was between 1.37 to 16.38 dS m-1, while the ECe (30 - 70 cm) was between 1.11 to 17.40 dS m-1. This research was expected to assist in the agricultural development planning, especially in wetlands which have been affected by the intrusion of sea water (salinity). Planning for theimplementation of the development of rice varieties that are sensitive to high and very high salinity. Planning and improvement of irrigation networks as sources of clean water for washing the salts or pushing salt water into the sea.Keywords: Coast of Indramayu, rice field, seawater intrusion, soil salinity